Administration of troxerutin and cerebroprotein hydrolysate injection alleviates cerebral ischemia/reperfusion injury by down-regulating caspase molecules - Sui R (Dove Medical Press, 2019)
Rubo Sui, Lie Zang, Yanjuan BaiDepartment of Neurology, The First Affiliated Hospital of Jinzhou Medical University, Jinzhou 121001, Liaoning, People’s Republic of ChinaCorrespondence: Rubo SuiDepartment of Neurology, The First Affiliated Hospital of Jinzhou Medical University, 2 Renmin Road, Jinzhou 121000, Liaoning, People’s Republic of ChinaEmail yaanddoy@sina.comBackground: Cerebral ischemia/reperfusion injury (I/R injury) is an important pathological process for nervous system. The I/R injury usually causes cerebral hypoxia, infarct or stroke. This study aimed to evaluate effects of troxerutin and cerebroprotein hydrolysate injection (TC) on I/R injury in rat models.Methods: Middle-cerebral artery occlusion/reperfusion (MCAO/R) rat models were established. Rats were divided into normal control (NC), MCAO/R rat model (injecting saline) and MCAO/R rats administrating with TC group (injecting with TC at concentration of 2 mL/100 g body weight). Neurological scores were evaluated with Garcia scale. Magnetic resonance imaging (MRI) was employed to observe infarct area, contralateral area and apparent diffusion coefficient (ADC) values. Cerebral infarct size was examined and visualized by staining with 2,3,5-triphenyltetrazolium chloride (TTC). Western blotting assay was used to determine caspase-1, caspase-3 and caspase-8 expression.Results: The infarct size of mice in MCAO/R+TC group was smaller significantly compared to that in MCAO/R group (p<0.05). The infarct/contralateral area ratio of T2 and T2 Flair signals in MCAO/R+TC group were lower significantly compared to that in MCAO/R group (p<0.05). ADC values in MCAO/R+TC group were significantly enhanced compared to that in MCAO/R group (p<0.05). The troxerutin and cerebroprotein treatment significantly increased neurological scores compared to that in MCAO/R group (p<0.05). Troxerutin and cerebroprotein treatment significantly decreased expression of caspase-1, caspase-3, caspase-8 compared to that in MCAO/R group (p<0.05).Conclusion: Troxerutin and cerebroprotein administration alleviated cerebral I/R injury by down-regulating caspase molecules.Keywords: ischemia/reperfusion injury, troxerutin and cerebroprotein hydrolysate injections, apoptosis, caspase